Usefulness of Suprahyoid Muscles Palpation during Repetitive Saliva Swallowing Test in Healthy and Dysphagic Adults - IKENO, Masahiro; KUMAKURA, Isami (The Japanese Journal of Dysphagia Rehabilitation, 2012)
The Repetitive Saliva Swallowing Test (RSST) is in widespread clinical use as a highly sensitive, low-risk method of screening for dysphagia. During evocation of the swallowing reflex, movement is observable in both the suprahyoid and infrahyoid muscles. However, conducting the RSST is challenging when laryngeal elevation cannot be confirmed due to thick cervical subcutaneous fat or high positioning of the thyroid cartilage. In this study, we investigated a possibility of improvement for the accuracy of RSST by concurrent palpation of the thyroid cartilage and the inferior aspect of the mandible. This hypothesis was verified by videofluorographic (VF) assessment of swallowing in addition to simultaneous measurement of surface electromyography (SEMG) and swallowing sounds. Methods included simultaneous measurement of SEMG, palpation of the thyroid cartilage, palpation of the inferior aspect of the mandible, and swallowing sounds in 23 healthy elderly subjects and 21 dysphagic patients. When the reflex was detected by palpation, a corresponding mark was made by the investigator on the SEMG. Muscle activity was calculated using integration after absolute value processing. SEMG was recorded from the suprahyoid and infrahyoid muscles. Comparison of the swallowing reflex marks made for swallowing sounds and during palpation revealed that the swallowing reflex detection rate was significantly increased by palpation of the suprahyoid muscles compared with thyroid cartilage palpation alone in healthy elderly subjects (97.5% vs 87.0%, respectively) and dysphagic patients (91.9% vs 81.0%, respectively). Furthermore, activation of the suprahyoid muscle group was significantly greater during evocation than during failed attempts. The effect of muscle fatigue over 30 seconds was not significant in this study. These findings suggest that the accuracy of RSST can be improved by concurrent palpation of the inferior aspect of the mandible in patients in whom confirmation of the swallowing reflex is difficult using thyroid cartilage palpation alone.